Functional mapping of a trypanosome centromere by chromosome fragmentation identifies a 16-kb GC-rich transcriptional “strand-switch” domain as a major feature - Obado, Samson O.; Taylor, Martin C.; Wilkinson, Shane R.; Bromley, Elizabeth V.; Kelly, John M. (Genome Research, 2005)
Trypanosomatids are an ancient family that diverged from the main eukaryotic lineage early in evolution, which display several unique features of gene organization and expression. Although genome sequencing is now complete, the nature of centromeres in these and other parasitic protozoa has not been resolved. Here, we report the functional mapping of a centromere in the American trypanosome, Trypanosoma cruzi, a parasite with an unusual mechanism of genetic exchange that involves the generation of aneuploidy by nuclear hybridization. Using a telomere-associated chromosome fragmentation approach, we show that the region required for the mitotic stability of chromosome 3 encompasses a transcriptional “strand-switch” domain constituted by a 16-kb GC-rich island. The domain contains several degenerate retrotransposon-like insertions, but atypically, lacks the arrays of satellite repeats normally associated with centromeric regions. This unusual type of organization may represent a paradigm for centromeres in T. cruzi and other primitive eukaryotes.
10.1101/gr.2895105